2006
DOI: 10.1002/chem.200600941
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilicities and Carbon Basicities of Pyridines

Abstract: Rate and equilibrium constants for the reactions of pyridines with donor‐substituted benzhydrylium ions have been determined spectrophotometrically. The correlation equation log k(20 °C)=s(N+E), in which s and N are nucleophile‐specific parameters and E is an electrophile‐specific parameter, has been used to determine the nucleophilicity parameters of various pyridines in CH2Cl2 and aqueous solution and to compare them with N of other nucleophiles. It is found that the nucleophilic organocatalyst 4‐(dimethylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
89
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 75 publications
(38 reference statements)
8
89
1
5
Order By: Relevance
“…[7] Previous results obtained computationally in gas phase and in ethanol at MP2(fc)/6-31G(d) level of theory (solvent polarizable continuum model) showed that the positive charge in the reactant ground state of benzhydrylpyridinium ions is distributed between the nitrogen atom and the methine carbon atom in a way that only 66 % of the positive charge is located on the nitrogen atom. [13] It has also been shown that the charge distribution is almost invariant of the substituents on the benzhydryl group or pyridine moiety. This observation is completely different from that obtained with sulfonium salts (tetrahydrothiophenium and dimethylsulfonium) in which the positive charge is almost completely located on the leaving group.…”
Section: Pyridinium Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Previous results obtained computationally in gas phase and in ethanol at MP2(fc)/6-31G(d) level of theory (solvent polarizable continuum model) showed that the positive charge in the reactant ground state of benzhydrylpyridinium ions is distributed between the nitrogen atom and the methine carbon atom in a way that only 66 % of the positive charge is located on the nitrogen atom. [13] It has also been shown that the charge distribution is almost invariant of the substituents on the benzhydryl group or pyridine moiety. This observation is completely different from that obtained with sulfonium salts (tetrahydrothiophenium and dimethylsulfonium) in which the positive charge is almost completely located on the leaving group.…”
Section: Pyridinium Saltsmentioning
confidence: 99%
“…Because of the invariant charge distribution of the partial charges in the reactant ground state of beznhydrylpyridinium salts with changing electrofugality, [13] it can be approximated that the stabilizations by solvation in all the reactant ground states are similar. Thus, solvent effects of pyridinium salts come from different solvation of the transition state.…”
Section: Pyridinium Saltsmentioning
confidence: 99%
“…Recent determination of nucleophilicity parameters for these two pyridines identified a large solvent effect, leading to higher nucleophilicities for PPY than for DMAP in dichloromethane, but to the reverse order in protic solvents such as H 2 O. [23] The combined presence of t-BuOH and acidic substrates may lead to a similar reduction of the intrinsically higher nucleophilic activity of PPY in this case. It should be added that the reaction proceeds extremely slowly in the absence of any of the pyridine bases (but with 2 equiv.…”
Section: Resultsmentioning
confidence: 96%
“…The limitations of Equations (1) and (2) will be illustrated below by correlations of kinetic data for reactions of benzhydrylium cations 1 and 2 [18][19][20][21] and for the methylvinylpyridinium cation 3.…”
mentioning
confidence: 99%